Spectrum of Surgical Presentation of Eosinophilic Enteritis - Spoorthy Sudhakar Shetty; Charan Kishor Shetty (Case Reports in Surgery)
Eosinophilic enteritis is a rare disorder presenting mostly with diarrhea, malabsorption, abdominal pain, weight loss, and hypersensitivity. Surgical manifestation of eosinophilic gastrointestinal disorders depends on the site and extent of involvement. In our case series of four patients two of them had ileocaecal masses with recurrent subacute intestinal obstruction with past history of intake of antitubercular drugs for 9 months. On histopathological examination both of them proved to have eosinophilic enterocolitis. Thus it is a clinical dilemma to differentiate between these two conditions. The other two patients presented as acute abdomen with perforation and intussusception. All four patients were treated surgically. Postoperatively they recovered well with no symptoms on one year follow-up. In Indian setup tuberculosis being rampant there may be under reporting or wrongly diagnosed cases of eosinophilic enteritis. Thus a strong clinical suspicion and awareness of this clinical entity are essential among surgical community.